Controlador Fuzzy aplicado a um sistema de controle de posição acionador por motores de indução trifásicos - Júlio, élida Fernanda Xavier (2010)
This work presents the project of fuzzy controllers for a X-Y coordinate table with two degrees of freedom. Both bases of the table moves horizontally, powered by tree-phases induction motors operated by frequency inverts. For detection position of bases, optical encoders were engaged to the axes of the engines to be obtained the angular displacement. A data acquisition board made the interface between a 1.4 GHz Pentium computer and the system. This board catches signals from the encoders and provides control signals to the frequency inverters. Fuzzy controllers, implemented im LabVIEM® software, determinate the control variables to power the engines. Step, sine and cosine reference were used to evaluate the system performance, in position control and following trajectory. Experimental results are presented.